PELVIC-FLOOR MUSCLE EXERCISES FOR THE IMPROVEMENT OF MALE SEXUAL FUNCTIONS - Máté PALANCSA; Miklós DAMÁSDI; Péter TARDI; Stefánia GITTA; Melinda JÁROMI; Pongrác ÁCS; Ágnes SIMON-UGRON; Márta HOCK (Cluj University Press, 2018)
Introduction. Premature ejaculation (PE) and erectile dysfunction (ED) are the most common sexual disorders among men regardless of ethnicity. The literature estimates the prevalence of PE between 16,3-32,5 and the prevalence of ED between 10-66% depending on age and secondary diseases. Objectives. We aim to assess the efficacy of the 8-week-long program of pelvic floor muscle(PFM) rehabilitation in the therapy of premature ejaculation and erectile dysfunctions. Materials and methods. The volunteer in our case-study was a 24-year-old, non-smoking, athletic university student living in a heterosexual, sexually active relationship for 5 months. At the beginning of the investigation, the subject had to complete numerous questionnaires. The trial used complex physiotherapy as treatment. The first part of the physiotherapy consisted of exercises to raise consciousness of the function of pelvic floor muscles (PFM). The patient had to learn how to isolate the contractions of PFM from its synergic muscles. The basic exercises consisted of isotonic, isometric and relaxation practices that lasted for 6 weeks. After that, "lifting exercises" supplemented the basic practices for another 2 weeks. Results. At the termination of the 8-week-long program all previously measured qualities showed improvement to a certain extent. Conclusion. At the end of the 8-week-long program, we measured significant change in various qualities regarding sexual life that proves the efficiency and the reason of existence of PFM rehabilitation in the therapy of premature ejaculation and erectile dysfunctions.